Development of an assay for determining PDE5 enzyme activity and for screening of potential inhibitors of the PDE5 enzyme in cancer cells - Granaas, Magnus Løkke (Universitetet i Tromsø, 2013)
PDE5 is a member of the superfamily of phosphodiesterases, and it is identified as the main mechanism for breakdown of cGMP in mammals. Sildenafil is a well-known inhibitor of the PDE5 enzyme and it is also shown that sildenafil inhibits the ABCC5 transporter pump. ABCC5 is a member of the superfamily of ABC-transporters, and identified as an important transporter for mediating the cellular efflux of cGMP. Research group of Pharmacology and Toxicology at University in Tromsø recently showed that sildenafil analogs, IS-39213 and IS-60049, almost completely blocked the cGMP efflux in cancer cell lines C33A and C-4I by inhibiting the ABBC5 transporter pump. It is not known if these sildenafil analogs also inhibit the PDE5 enzyme. To further investigate this, an assay was developed for determining PDE5 activity and for screening of these potential inhibitors on the PDE5 enzyme in cancer cell lines C-4I and C-33A. Both IS-39123 and IS-60049 were shown to inhibit the PDE5 enzyme in the same degree as sildenafil, but the time available did not allow completion of the characterization of inhibitors and their mutual potency.